Edytorska lektura tomików wierszy Jerzego Ficowskiego, Elżbiety i Witolda Szwajkowskich, Agnieszki Frączek i innych w kontekście ćwiczeń logopedycznych - Ostasz, Maria; Pastuła, Marta (Dydaktyka Polonistyczna, 2018)
The article is an attempt to look at a few selected volumes for a child’s addressee, which allows to indicate the aspects of evaluation to the buyers of such editions, and to the publishers to forecast the accuracy of composing such publications. The editorial reading was based on volumes of poems by Jerzy Ficowski, Elżbieta and Witold Szwajkowski, Marcin Brykczyński and Agnieszka Frączek in the context of speech therapy exercises. This editorial reading, also colloquially understood as “reading activity”, focused on the following phenomena: – bold, – italics, – highlighting with colour, – placing the text on a coloured background, – moving the information about the practised phonic sounds onto the margin, – placing the information about the practised phonic sounds and the age of the child in a live page, – font selection (serif/sans-serif), – change of the letter depending on the recipient of a given paragraph, etc. The observations concern the power of the educational (speech therapy) influence of the editorial aterial or the materiality of the book in the meaning of Roland Reuß. One can also try to say that this series of distinctions facilitates working with the text both for the speech therapist and the child. However, one should pay attention to the entire editorial and child-perspective of such editions. Not only the way of distinction itself is important, but the correspondingly clear contrasts between the used colours, writing degrees, spacing, etc. are preserved, remembering the fun and educational function of the type of publication for the child as a recipient, especially with speech therapy deficits.